Axonal Segregation and Role of the Vesicular Glutamate Transporter VGLUT3 in Serotonin Neurons - Voisin, Aurore N.; Mnie-Filali, Ouissame; Giguère, Nicolas; Fortin, Guillaume M.; Vigneault, Erika; El Mestikawy, Salah; Descarries, Laurent; Trudeau, Louis-Éric (Frontiers in Neuroanatomy, 2016)
A subset of monoamine neurons releases glutamate as a cotransmitter due to specific expression of the vesicular glutamate transporters VGLUT2 or VGLUT3. In addition to mediating fast synaptic excitation, it has been proposed that VGLUT3 enhances serotonin (5-HT) vesicular loading by the vesicular monoamine transporter (VMAT2) in 5-HT neurons. In dopamine (DA) neurons, glutamate appears to be released from specialized subsets of terminals and it may play a developmental role, promoting neuronal growth and survival. The hypothesis of a similar developmental role and axonal localization of glutamate co-release in 5-HT neurons has not been directly examined. Using postnatal mouse raphe neurons in culture, we first observed that in contrast to 5-HT itself, other phenotypic markers of 5-HT axon terminals such as the 5-HT reuptake transporter (SERT) show a more restricted localization in the axonal arborization. Interestingly, only a subset of SERT- and 5-HT-positive axonal varicosities expressed VGLUT3, with SERT and VGLUT3 being mostly segregated. Using VGLUT3 knockout mice, we found that deletion of this transporter leads to reduced survival of 5-HT neurons in vitro and also decreased the density of 5-HT-immunoreactivity in terminals in the dorsal striatum and dorsal part of the hippocampus in the intact brain. Our results demonstrate that raphe 5-HT neurons express SERT and VGLUT3 mainly in segregated axon terminals and that VGLUT3 regulates the vulnerability of these neurons and the neurochemical identity of their axonal domain, offering new perspectives on the functional connectivity of a cell population involved in anxiety disorders and depression.